2019
DOI: 10.1098/rspb.2018.2840
|View full text |Cite
|
Sign up to set email alerts
|

Common Caribbean corals exhibit highly variable responses to future acidification and warming

Abstract: We conducted a 93-day experiment investigating the independent and combined effects of acidification (28023300 matm pCO 2 ) and warming (288C and 318C) on calcification and linear extension rates of four key Caribbean coral species (Siderastrea siderea, Pseudodiploria strigosa, Porites astreoides, Undaria tenuifolia) from inshore and offshore reefs on the Belize Mesoamerican Barrier Reef System. All species exhibited nonlinear declines in calcification rate with increasing pCO 2 . Warming only reduced calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 77 publications
10
65
2
Order By: Relevance
“…However, P. strigosa was the only species that exhibited reduced 566 calcification under elevated temperature, which is consistent with results present here and 567 highlights that thermal stress more negatively impacts P. strigosa than S. siderea ( Figure 5D-F). 568 Bove et al (2019) also found that S. siderea was the most resistant of the four species studied, as 569 it was able to maintain positive calcification rates even in the most extreme acidification 570 treatment (~3300 ߀ atm pCO 2 )-findings that are also corroborated here (Figure 2A). 571…”
Section: (34) Pseudodiploria Strigosa Trait Correlations 482supporting
confidence: 73%
“…However, P. strigosa was the only species that exhibited reduced 566 calcification under elevated temperature, which is consistent with results present here and 567 highlights that thermal stress more negatively impacts P. strigosa than S. siderea ( Figure 5D-F). 568 Bove et al (2019) also found that S. siderea was the most resistant of the four species studied, as 569 it was able to maintain positive calcification rates even in the most extreme acidification 570 treatment (~3300 ߀ atm pCO 2 )-findings that are also corroborated here (Figure 2A). 571…”
Section: (34) Pseudodiploria Strigosa Trait Correlations 482supporting
confidence: 73%
“…Meanwhile, observations of elevated growth rates relative to lower variability sites and increasing and/or stable growth rates through time on reefs exposed to higher degrees of environmental variability (e.g., temperature and/or nutrients) indicate that exposure to environmental variation may precondition coral populations (Carilli, Donner, & Hartmann, 2012;Carricart-Ganivet & Merino, 2001;Castillo, Ries, Weiss, & Lima, 2012;Manzello, Enochs, Kolodziej, & Carlton, 2015) potentially affording them greater resilience in the face of more frequent and/or more intense thermal stress events. Changing seawater chemistry (i.e., ocean acidification) may also lead to lower coral growth rates (e.g., Bove et al, 2019;Chan & Connolly, 2013). Temporal trends in coral growth rates at any given location are dependent upon a complex network of factors due to the interactive nature of environmental variables known to influence calcification (Courtney et al, 2017;Jokiel & Coles, 1977;Pratchett et al, 2015).…”
mentioning
confidence: 99%
“…Although ocean warming caused reduced calcification of Caribbean corals in the included studies, the combination of acidification with warming was not clearly different from the two independent stressors (Crain et al, 2008). Because only four studies tested the combination of acidification and warming (Towle et al, 2015;Horvath et al, 2016;Okazaki et al, 2017;Bove et al, 2019), however, the sample size for the interaction term was very low. With this small samples size in conjunction with only about 17% of Caribbean reef-building coral species analyzed in the current study, the potential for synergistic or additive effects should not be ignored.…”
Section: Discussionmentioning
confidence: 89%
“…It is therefore likely that corals included in this meta-analysis that did not exhibit reduced calcification rates in association with simulated ocean acidification may have stronger control of their calcifying fluid to maintain comparable growth rates. Overall, corals from the studies included in the current meta-analysis exhibited variable responses under experimental seawater acidification, highlighting the diversity of responses to stress on the individual and species levels (Comeau et al, 2014;Okazaki et al, 2017;Bove et al, 2019).…”
Section: Discussionmentioning
confidence: 96%